2019
DOI: 10.1093/carcin/bgz142
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation of SOX5 by Brachyury promotes breast cancer bone metastasis

Abstract: Abstract The bone marrow has been long known to host a unique environment amenable to colonization by metastasizing tumor cells. Yet, the underlying molecular interactions which give rise to the high incidence of bone metastasis (BM) in breast cancer patients have long remained uncharacterized. In our study, in vitro and in vivo assays demonstrated that Brachyury (Bry) could promote breast cancer BM. Bry drives epithelial–mesenchymal transition (EMT) and promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 46 publications
5
29
0
Order By: Relevance
“…Silencing of BRACHYURY in breast MDA-MB-436 cells statistically significantly reduced the ability to invade the ECM and form mammospheres in primary and secondary cultures (9). Our study (60) demonstrated that BRACHYURY promoted breast cancer cell invasion, migration, adhesion, and colonization in bone microenvironment in vitro, and BRACHYURY knockdown in MDA-MB-231 cells decreased the colonization and survival capability in bone tissue in vivo. BRACHYURY-high breast tumor cells were more resistant to the cytotoxic effects of docetaxel in vitro (9).…”
Section: Breast Carcinomasupporting
confidence: 51%
See 3 more Smart Citations
“…Silencing of BRACHYURY in breast MDA-MB-436 cells statistically significantly reduced the ability to invade the ECM and form mammospheres in primary and secondary cultures (9). Our study (60) demonstrated that BRACHYURY promoted breast cancer cell invasion, migration, adhesion, and colonization in bone microenvironment in vitro, and BRACHYURY knockdown in MDA-MB-231 cells decreased the colonization and survival capability in bone tissue in vivo. BRACHYURY-high breast tumor cells were more resistant to the cytotoxic effects of docetaxel in vitro (9).…”
Section: Breast Carcinomasupporting
confidence: 51%
“…BRACHYURY/BRACHYURY expression has been reported to positively associate with the invasive and metastatic capability of breast carcinoma cells in vitro and with the risk of recurrence and distal metastasis in breast patients (9,60). Different studies have demonstrated the potential of BRACHYURY as a target for the treatment of breast carcinoma using cancer vaccines or immunotherapy approaches (61,62).…”
Section: Breast Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…The human brachyury protein (Bry), the transcriptional factor regulating posterior mesoderm formation and notochord differentiation, has been reported as a specific and sensitive marker ( 2 5 ) and a master regulator of the oncogenic transcriptional network of chordoma ( 6 ). Further studies demonstrated up-regulation of brachyury gene occurs in various human tumors of epithelial origin, including lung, breast, colorectal, prostate cancer and others, but not in the majority of normal adult tissues ( 7 9 ). In primary lung carcinoma samples, brachyury mRNA expression was identified as a significant predictor in 5 year disease free survival and overall survival rate ( 10 ) and positively correlated with tumor stage and poor prognosis ( 8 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%